Measurement of Electron Density and Temperature in Laser Induced Stainless Steel (SS) Plasma (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2017)
In this present work, electron temperature and electron density in Laser Induced Plasma (LIP) of Stainless Steel (SS) in air as a function of laser energy is presented. The emitted lines of Fe I at 351.0 nm, 373.5 nm, 397.5 nm are identified in LIP of SS. The electron temperature is obtained via Boltzmann plot from the relative intensity of these emitted lines. Electron density was determined from the stark broadening of Fe~I lines at 375.5 nm. The electron density and temperature were measured at three different laser energies; 50 mJ, 60 mJ and 70 mJ. The electron temperature and electron density are found to be 0.145, 0.149 and 0.141 eV and \(2.64× 10 ^{18}\), \(2.66× 10 ^{18}\) and \(2.54×10 ^{18}\) cm\(^{-3}\), respectively. The fall in both parameters can be explained due the plasma shielding effect at high energyof laser beam.
Keywords: LIBS; Plasma temperature; Electron density; Boltzmann plot; Stark broadening